Medical Anthropology: A Review - Veena Bhasin (Ethno-Med., 1(1): 1-20 (2007), 2007)
Medical anthropology looks at cultural conceptions of the body, health and illness. Medical anthropology is the study of ethno-medicine; explanation of illness and disease; what causes illness; the evaluation of health, illness and cure from both an emic and etic point of view; naturalistic and personalistic explanation , evil eye, magic and sorcery; biocultural and political study of health ecology; types of medical systems; development of systems of medical knowledge and health care and patient-practitioner relationships; political economic studies of health ideologies and integrating alternative medical systems in culturally diverse environments. Ethnomedicine also refers to the study of traditional medical practice. Theoretical classic-Medicine, Magic and Religion defined medicine as a cultural system. In Puerto Rico, spiritism offers a traditional alternative to community health services. Two systems of health care co-exist in Ecuador. Health care in India is charaterised by medical pluralism, including self care, consultations with traditional healers and /or primary health care services (PHCs) These medical systems are complementary, alternative and unconventional. In addition to codified traditional systems- Ayurvedic, Unani and Siddha there is ethno-medicine, religious healing and folk medicine. Indian medical policy is not based on traditional medicine alone. The state health programmes are well intended but lack anthropological consultation. To date, research into traditional medicine has been covered mainly by anthropology and it is suggested that other scientific disciplines should be incorporated in order to further rescue and revalue this part of the cultural heritage that has contributed substantially to human health and to the development of indigenous medical knowledge and its resources.